(untitled) (American Journal of Islam and Society, 2003)
Many books have been written on Muslims and Islam since 9/1 I. A majority of them have tried to show Islam’s negative side in an attempt to prove that Islam teaches violence and that Muslims love to engage in jihad to become martyrs. Such contentions are generally made by antiMuslim interest groups, certain religious organizations, and politicians under the influence of such extremists. These people stir up anti-Muslim sentiments to influence public opinion and bend government policies in favor of such groups. This book is a similar attempt to gain popularity for the authors and arouse anti-Muslim sentiment at a time that is trying for most Americans. The authors, Ergun Caner and Emir Caner, are brothers. The senior author is professor of theology at Criswell College, Dallas, Texas, and the second author teaches at the Baptist Seminary in Wake Forest, North Carolina. The book contains a preface and introduction, I 6 chapters on various aspects of Islam, and four appendices, including an index to the Qur’an and a glossary of Arabic terms. The preface is a story of the clash ofcultures between the authors’ Muslim (Turkish) father and Swedish mother, which resulted in a divorce when the Caner brothers were still very young. The father had visitation rights and would take Ergun and Emir to the Islamic Center in Columbus, Ohio, on weekends "to do the prayers, celebrate Ramadhan and read the Qur’an." This was the children’s only exposure to Islam, until Ergun was I 5 and visited a church after his best friend invited him to do so. Ergun found the people at church warm and "didn’t mock when he stumbled through the hymns." He joined the gospel ministry in 1982 and has since been preaching (against Islam) in order "to bring salvation for 1.2 billion Muslims." Thus the title of the book is itself deceiving, as it conveys that a practicing Muslim became a Christian, when, in fact, the authors actually became Christians in their early teens and had almost no education in Islam. It is appalling that the introductory chapter opens with a threat from "Shaikh" Osama bin Laden to the Americans and blessings for those who gave their lives to k.ill the 9/1 I victims. The authors portray bin Laden as a typical Muslim who is out to get all people who refuse to accept Islam ...